Cognitive and Functional Outcomes of Early Versus Delayed Cranioplasty after Decompressive Craniectomy - Kumar, Arun; Nayak, Biswaranjan; B. H, Krishnamurthy; Patro, Sushant Kumar; C. R, Abhijeet; Singh, Balwant; Nayak, Himanshu Bhusana; Shukla, Dhanwantari; Biswal, Debabrat; Sahoo, Prafulla Kumar (Indian Journal of Neurotrauma, 2018)
Introduction Delay in doing cranioplasty (CP) after decompressive craniectomy (DC) may cause motor, cognitive, and language deficits. Studies show doing CP before developing such symptoms helps in improving the outcome. CP improves cerebrospinal fluid (CSF) dynamics and cerebral blood flow, which may lead to better cognitive and functional outcome.Objective The aim of the study was to assess cognitive and functional outcomes of early versus delayed cranioplasty (DCP) after DC.Methodology This was a prospective observational study on 42 patients aged over 16 years and up to 70 years, who had undergone CP after DC for severe traumatic brain injury in in-patient and outpatient department of neurosurgery at a tertiary care hospital in Bhubaneswar, Odisha, India from the period of March 01, 2016 to December 31, 2017. Cognitive and functional outcomes were compared in early and DCP groups in preoperative and follow-up period at 1 month, 3 months, and 6 months. Early cranioplasty (ECP) was within 2 months, and DCP was beyond 2 months.Results Total sample size under this study was 42; 21 in ECP and 21 in DCP group. Mean age was 41.40 ± 15.95 years. The age distribution was quite young with 38.1% in 30 to 49 age group and had very high proportion of males (85.7%). This analysis revealed that both the ECP and DCP groups have resulted in significant improvement in mini-mental state examination (MMSE) and Glasgow Outcome Scale Extended (GOSE) score after CP. But in the ECP group, there has been steady and significant improvement in MMSE and GOSE score at different follow-ups starting from postoperative 1 month in MMSE score and from 3 months up to 6 months in GOSE score.Conclusion Neurosurgeon should evaluate and carefully monitor each individual case and take up CP as early as possible with suitable indication.
Keywords: decompressive craniectomy; early cranioplasty; delayed cranioplasty; cognitive outcome; functional outcome